Rancang Bangun Aplikasi Informasi Perkuliahan Berbasis Android - Irma Salamah; Lindawati Lindawati; Herlina Fitri Handayani (STIKOM Tunas Bangsa Pematangsiantar, 2019)
Nowaday, the development of smartphone technology is increasingly popular. Android as one of the operating systems of mobile devices, provides tools and API for Android developers to develop applications. At universities, smartphone use is popular among students. Through smartphones, the use of mobile and web applications is more effective and efficient with the ease of delivery and receipt of information. In this study, the author made a mobile application that contains academic informations that complements the class schedule, the final semester exam schedule, incidental schedules, academic calendar and the latest announcements with push notification as a reminder for students. With this application it is expected that students can access and obtain the latest information anywhere more easily.